Examining the Impact of Socio-Economic Characteristics on Commuting Patterns and Transportation Among University Students in Ogun State, Nigeria - Gbadebo S. O; Ogundele E. O (Darul Yasin Al Sys, 2025)
This study presents a comprehensive demographic and transportation analysis of students and staff at Bells University and Covenant University, examining commuting patterns in relation to socio-economic characteristics such as age distribution, marital status, and income levels. Results indicate that Covenant University has a higher proportion of younger respondents (38% aged 15–18) compared to Bells University (28%), with the majority at both institutions being single (77% at Bells; 83% at Covenant), reflecting a predominantly young, unmarried student population. Income data show that 56.5% of Bells staff earn above ₦114,000, while 44% of Covenant students receive allowances between ₦30,001 and ₦50,000. Trip analysis reveals that most journeys are under 30 minutes (69% at Bells; 76% at Covenant), with longer trips over one hour accounting for 17% and 11%, respectively. Car use is higher at Covenant, reflecting greater access to private vehicles, while walking and public transport use remain relatively low at both institutions. Trip purposes shift over the day, with initial trips primarily for educational purposes, especially at Covenant followed by increased shopping and recreational travel, suggesting a balance between academic and social activities. The findings highlight the need for targeted, sustainable transportation policies that address the mobility needs of university communities while enhancing campus accessibility and livability.